Development of Picture Storybooks to Improve Students' Independent Character in Pancasila Education Learning - Aisyah Putri Salsabila; Titin Sunaryati (Pusdikra-Publishing.com, 2024)
The objectives of this study are: (1) describe the contents of picture story book products; (2) explain the using of picture story book media; (3) analyze the teacher and student responses of picture story book as a media for learning; (4) clarify the effectiveness of picture story book media. This research was conducted on May – August 2023 of 27 students in SDIT As-Sabiquun of grade 1. The research on this study is used the Research and Development (R&D) method, which include the ADDIE development model in 5 steps. From the results of the feasibility test conducted by three validators, such as media expert, linguistic expert, and media materials expert, picture storybooks obtained an average percentage of 90% With a very decent category. The results of the teacher's response obtained an average percentage of 87%, meanwhile the results of student response in questionnaires for individual trials gained a percentage of 97.2%, besides small group tests obtained a percentage of 94.3%, and large group tests obtained a percentage of 95.3%. The results before and after treatment calculated using N-gain increased by 0.5 and reached medium category. So the conclusion is the development of picture storybook as media of learning are feasible, practical, and effective to improving the students' independent character for grade 1 in primary school.